PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE BERORIENTASI KEGIATAN LABORATORIUM TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA SMAN 2 PADANG PANJANG - Hilda Wahyuni (PILLAR OF PHYSICS EDUCATION, 2014)
Physics learning activities in senior high school was still dominated by conventional methode which cause student’s low interest in learning physics. Consequently, these problems cause low learning outcomes of the students. One of the solution of these problems was by using “learning cycle” model which also followed by doing experimental activities in laboratory. This research was an experimental research randomize control group only design. The population of this research were all of the students of SMAN 2 Padang Panjang in the second semester of academic year 2013/2014. The data of the research were the student’s learning outcomes in the area of cognitive, affectif, and phychomotor. The research’s instrument are test sheet (multiplier choice and essay) for cognitive domain, observation sheet for affective domain, and score rubric for psychomotor domain. The result of this research showed that the mean score of the experimental class was higher then control class. Based on the data analysis result, it was gotten that there was significance different learning outcomes between experimental and control class at 0,05 significance level. It showed that using learning cycle which laboratory activies orientation influence students of SMAN 2 Padang Panjang learning outcomes in learning physics